National Health and Nutrition Examination Survey III, 1988-1994 ([Verlag nicht ermittelbar], 1998)
The third National Health and Nutrition Examination Survey (NHANES III), conducted in 1988-1994, was designed to obtain nationally representative information on the health and nutritional status of the population of the United States through interviews and direct physical examinations. NHANES III contains data for a sample of 33,994 persons aged 2 months and older who participated in the survey. A home examination option was employed for the first time in order to obtain examination data for very young children and for elderly persons who were unable to visit the mobile examination center (MEC). The home examination included only a subset of the components used in the full MEC examination, since it would have been difficult to collect some types of data in a home setting. The dataset contains information on high blood pressure and cholesterol, obesity, passive smoking, lung disease, osteoporosis, HIV, hepatitis, helicobacter pylori, immunization status, diabetes, allergies, growth and development, blood lead, anemia, food sufficiency, and dietary intake, including fats, antioxidants, and nutritional blood measures. Dietary Recall information is found in three data files (Parts 4, 7, and 8) and four table files (Parts 3, 5, 6, and 9). The Adult and Youth Household files (Parts 1 and 11) comprise the total number of respondents when combined. All of the data files may be linked by using the survey participant identification number (SEQN).